MOTIVASI MAHASISWA BERORGANISASI DI KAMPUS - Niken Cahyorinartri (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
The aim of this study is to describe the student’s motivation in participating in student organizations at Universitas Jenderal Achmad Yani. This study uses self-determination theory to explain the motivation of students to involve in student organizations. Self-determination theory explained that human motivations were important sources in the development of personality and self-regulation. The motivation involved the reasons and the purposes in performing an action. Motivation moves from extrinsic motivations to intrinsic motivations. The method of this study was quantitative descriptive research. Participant of this research were college students who participating in students organizations. The result showed that most of the students participated in student organizations had integration extrinsic motivation. Students involved in the student organizations because they interested and it gived them some benefits. Draw the benefits in students organizations become the majority reasons of the students in participating in the student organizations.